Investigation on the printability of bioink based on alginate-gelatin hydrogel and liquid crystals - Alyaa Idrees Abdulmaged; Chin Fhong Soon; Balkis A. Talip; Sheril Amira Othman; Gim Pao Lim; Kian Sek Tee (Institute of Advanced Engineering and Science, 2020)
Bioinks of 3D bioprinting have significant potential application in the field of tissue engineering to support cell attachment and proliferation. In this work, the alginate-gelatin-CELC (AGLC) bioink based on different compositions of alginate-gelatin (AG) hydrogel and cholesteryl ester liquid crystals (CELC) was prepared. Primarily, the alginate-gelatin hydrogel with certain concentration of gelatin (10-50%w/v) was investigated. The printability of the hydrogel reached a minimum width of 1.8 mm at a flow rate of 1 mL/min when the gelatin concentration was increased to 50% w/v (AG1050). Subsequently, the respective polymers with 10% w/v alginate and 50% w/v gelatin blended with 1%, 5%, 10%, 20%, 40%, and 60% w/v of CELC in the preparation of the alginate-gelatin-CELC bioink was further investigated.The printability of the bioink was examined by micro-extrusion based 3D bioprinter. The printability of the bioink enhanced by 27.8% as compared to AG1050 and reached a minimum width of 1.3 mm at a flow rate of 1 mL/min when the CELC concentration was increased to 40% and 60%. The tested properties of the bioink show that the CELC improve shear-thinning and lipid moieties properties to the composite bioink and hence, enhances its printability.